2007
DOI: 10.1039/b704041e
|View full text |Cite
|
Sign up to set email alerts
|

FTIR spectroscopy and thermodynamics of hydrogen adsorbed in a cross-linked polymer

Abstract: The adsorption of H(2) in a cross-linked poly(styrene-co-divinylbenzene) (St-DVB) microporous polymer (BET surface area 920 m(2) g(-1)) is studied by volumetric and gravimetric methods, FTIR spectroscopy at variable temperature (300-14 K) and ab initio calculations. At 77 K the polymer reversibly stores up to 1.3 mass% H(2) at a pressure of 1 bar and 1.8 mass% at 10 bar. The adsorption process involves the specific interaction of H(2) with the structural phenyl rings through weak dispersive forces. The interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 62 publications
4
47
1
Order By: Relevance
“…By infrared studies Spoto et al showed that the adsorption of hydrogen on a porous poly(styreneco-divinylbenzene)polymer involves the specific interaction of the H 2 molecule with the phenyl ring with an interaction energy of $0.4 kJ mol À1 which is comparable with the interaction energy between H 2 and activated carbon [71]. This interaction may be increased in narrower pores where hydrogen can interact with more than one pore wall, as suggested by Wood et al [10].…”
Section: Organic Polymerssupporting
confidence: 54%
“…By infrared studies Spoto et al showed that the adsorption of hydrogen on a porous poly(styreneco-divinylbenzene)polymer involves the specific interaction of the H 2 molecule with the phenyl ring with an interaction energy of $0.4 kJ mol À1 which is comparable with the interaction energy between H 2 and activated carbon [71]. This interaction may be increased in narrower pores where hydrogen can interact with more than one pore wall, as suggested by Wood et al [10].…”
Section: Organic Polymerssupporting
confidence: 54%
“…Most studies will be devoted to hydrogen sorption, also due to the interesting preliminary results of hydrogen absorption in crosslinked microporous amorphous polystyrene [109]. Modeling studies will be conducted also on ethylene sorption and dynamics, also in the attempt to rationalize recent results which have shown that d form s-PS films are suitable for (also repeated use) food packaging requiring ethylene (well known fruit ripening hormone) removal [68].…”
Section: Discussionmentioning
confidence: 98%
“…The rotational-vibration bands features of para hydrogen are located at 4505 and 4842 cm À1 . However, the vibrational band feature of para hydrogen (4161 cm À1 ) was absent in our present study [52]. As the catalysts calcination temperature decrease, the intensity of bands 4152 and 4739 cm À1 was gradually decreased.…”
Section: Effect Of Calcination Temperature and Supportmentioning
confidence: 47%